The stigma of alcohol use during pregnancy: Exploring the impact of alcohol strength and social context on public perceptions - Sam Burton; Shannon Cummings; Charlotte Connides-Smith; Elizabeth Fairweather; Catharine Montgomery; Abigail K. Rose; Poppy Whalley; Andrew Jones (PLoS ONE, 2026)
Alcohol use during pregnancy remains a major public health concern, with societal expectations of abstinence often resulting in stigma toward women who drink. To examine stigma and discrimination attributed to pregnant women consuming alcohol of varying strength and social context, within hypothetical scenarios. We explored whether greater stigma was attributed to consuming alcohol in social settings vs. alone, and whether consumption of low and alcohol-free drinks are less stigmatised than standard strength alcohol drinks. The research employed a vignette-based experimental design across three studies, involving hypothetical social scenarios depicting alcohol consumption during pregnancy. Participants were randomly assigned to alcohol (3 levels: no, low and standard alcohol) and social context (2 levels: alone or with friends) conditions recruiting a total of 1,054 participants. Measures of stigma were assessed using the Stigma and Attribution Assessment (SAA) and Personal and Perceived Public Stigma Measure (PPSM). Discriminatory behaviour was measured in two studies using a novel discrimination task. Pregnant women consuming standard and low-alcohol drinks were more stigmatised than those consuming alcohol-free beverages across multiple aspects of stigma. Pooled analyses showed that standard alcohol was associated with greater stigma on measures including social distance, perceived danger, prognostic optimism, public stigma, and personal discrimination. Low-alcohol drinks were also more stigmatised than alcohol-free drinks across domains such as blame, continued care, public stigma, and treatment stigma. The stigma attributed to women consuming alcohol during pregnancy may vary as a function of alcohol strength, with consumption of alcohol-free products associated with least stigma. Stigma attribution seemed driven by societal norms around abstinence. Public health messaging should shift towards risk-informed education to shape societal norms of abstinence and reduce stigmatisation.